Challenges and Opportunities in Shipyard Industry Financing in Indonesia: A SWOT Analysis Comparing Batam and Non-Batam Clusters - Zulfakhri, Ahlan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Indonesia's maritime sector plays a crucial role in the national economy, particularly through shipyard activities spread across both Batam and non-Batam areas. This research examines the financial landscape of the shipbuilding industry in these regions, assessing the challenges, opportunities, strengths, and weaknesses that shape its development. Given its strategic location in Southeast Asia and abundant natural resources, Indonesia has the potential to become a key player in the global maritime industry. However, significant barriers such as high interest rates and limited banking services continue to hinder growth. In Batam, the presence of local policy support and Islamic financing mechanisms from institutions like Bank Mandiri and Bank Permata Syariah offers notable benefits, despite the inherent risks associated with reliance on regional policies. Conversely, non-Batam areas benefit from financial backing by international entities like the Mizuho Group, providing a broader range of long-term funding options. Nevertheless, these regions still face challenges related to infrastructure constraints and elevated interest rates. A SWOT analysis highlights the necessity of implementing adaptable financing strategies and maintaining consistent policy support to ensure sustainable expansion of the shipyard industry across both regions.